Thermographic investigation of the effect of plasma exposure on the surface of a MAST upgrade divertor tile in Magnum-PSI. (December 2020) - Dunn, M.J.; Morgan, T.W.; Genuit, J.W.; Loewenhoff, T.; Thornton, A.J.; Gibson, K.J.; ,
Abstract: One of the issues faced by future fusion devices will be high divertor target heat loads. Alternative divertors can promote detachment, flux expansion and dissipation mechanisms to mitigate these heat loads. They have been investigated in several devices including TCV and DIII-D, and will be investigated on MAST-U. To evaluate their effectiveness, accurate target heat flux and power balance measurements are required in these machines. Infrared (IR) thermography is a widely used technique to determine the target heat flux, but is susceptible to surface effects and emissivity in carbon-walled machines. In this work, the effect of plasma exposure on graphite is assessed to understand what may happen in MAST-U. A sample of fine grain graphite, as used on MAST-U, is exposed to 30min plasma exposures, with density  n e = 6  ×  1018 m−3 and temperature  T e = 0.08 eV as measured by Thomson scattering. During these pulses, the temperature is measured by a medium wave IR camera and is seen to decrease by  ≈ 70 °C over the course of 3h of plasma exposure. Pyrometer measurements suggest that the IR camera data is affected by a change in the surface emissivity. Profilometry confirms erosion of graphite at the tile centre to a depth of  ≈ 100 µm, and a larger region of deposition further out, amounting to  ≈ 40 µm of material. Highlights: A graphite tile from MAST-U was exposed to plasma in Magnum-PSI. Apparent temperature decrease of 70°C was reported over the course of 3h. Multiwavelength pyrometry confirms that temperature did not actually decrease. Apparent change was caused by lower emissivity. Surface topology reveals lower emissivity caused by erosion of tile surface.